Systematic literature review: Theory perspective in green procurement - Yunus, Rafiuddin Mohd; Aripin, Norhana Mohd; Fauzi, Muhammad Ashraf; Alimin, Nur Sofia Nabila; Yusuf, Muhammad Fakhrul (Edelweiss Applied Science and Technology, 2025)
This paper presents a literature review of the theoretical background in green procurement research, aiming to enhance comprehension of the role of theory in the sustainable purchasing decision-making process. According to the PRISMA 2020 guidelines, we searched peer-reviewed journal articles that directly applied theory in Scopus and Web of Science, and identified 52 articles. Descriptive statistics indicate a significant increase in the number of publications based on theory since 2015, with a notable concentration in journals focused on sustainability and operations. The most prevalent theories are the RBV/NRBV, Institutional Theory, and Stakeholder Theory, while Contingency Theory, Transaction Cost Economics, Dynamic Capabilities, and Social Exchange appear to be less widespread. One-third of the studies combine two or more theories; the majority of these are single-lens-based studies. The field is both internal and external in its explanations, and theoretically narrow, with very little dependence on circular economy, sociotechnical, and behavioral approaches. To augment cumulative knowledge and practice, our suggestions are diversified and integrative theorizing, greater geographic coverage, and longitudinal/mixed-method design. The scholars and practitioners are enlightened by these lessons to develop stronger and more theory-oriented procurement research agendas.